Shoulder Interfascial Plane Blocks as sole Anaesthesia for Frozen Shoulder Manipulation - Syahrul Mubarak Danar Sumantri (Majalah Anestesia & Critical Care, 2020)
Passive manipulation for patients with frozen shoulder may enable fast recovery of shoulder symptoms. For the concern of many clinicians that deep anaesthesia and sedation for frozen shoulder manipulation may carry certain difficulty in identifying pericapsular structures damage during the procedure, we proposed a novel shoulder interfascial plane blocks for awake frozen shoulder manipulation.